Want this question answered?
Be notified when an answer is posted
x2 + 4x = x(x+4)
x2 + 4x = x(x + 4)
2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2
x(4x-2)
20
Yes. 4x means 4 multiplied by x. x4 means x multiplied by x multiplied by x multiplied by x.
(X2) (X2) = X4 x squared multiplied by x squared is x raised to the 4th power.
When you multiply 4x² by 4x², you multiply the coefficients (4 * 4 = 16) and add the exponents of the variables (x² * x² = x^(2+2) = x⁴). Therefore, the result is 16x⁴.
x2 + 4x = x(x+4)
x2 + 4x = x(x + 4)
4x^2 = 2 * 2 * x * x
(4x - 7y)(4x + 7y)
2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2
x(x-4)
x(4x-2)
It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.
20